Predictors of Complication Following Cleft Lip and Palate Surgery in a Low-Resource Setting: A Prospective Outcomes Study in Nicaragua. (December 2022) - Swanson, Marco A.; Auslander, Allyn; Morales, Tatiana; Jedrzejewski, Breanna; Magee, William P.; Siu, Armando; Ayala, Ruben; Swanson, Jordan W.
Background: Higher rates of postoperative complication following cleft lip or palate repair have been documented in low resource settings, but their causes remain unclear. This study sought to delineate patient, surgeon, and care environment factors in cleft complications in a low-income country. Design: Prospective outcomes study. Setting: Comprehensive Cleft Care Center. Patients: Candidate patients presenting for cleft lip or palate repair or revision. Interventions: Patient anthropometric, nutritional, environmental and peri- and post-operative care factors were collected. Post-operative evaluation occurred at standard 1-week and 2-month postoperative intervals. Main Outcome Measures: Complication was defined as fistula, dehiscence and/or infection. Results: Among 408 patients enrolled, 380 (93%) underwent surgery, of which 208 (55%) underwent lip repair (124) or revision (84), and 178 (47%) underwent palate repair (96) or revision (82). 322 (85%) were evaluated 1 week and 166 (44%) 2 months postoperatively. 50(16%) complications were identified, including: 25(8%) fistulas, 24(7%) dehiscences, 17(5%) infections. Mid-upper arm circumference (MUAC) ≤12.5 cm was associated with dehiscence after primary lip repair (OR = 28, p = 0.02). Leukocytosis ≥11, 500 on pre-operative evaluation was associated with dehiscence (OR = 2.51, p = 0.04) or palate revision fistula (OR = 64, p < 0.001). Surgeons who performed fewer previous-year palate repairs had higher likelihood of palate complications, (OR = 3.03, p = 0.01) although there was no difference in complication rate with years of surgeon experience or duration of surgery. Conclusions: Multiple patient, surgeon, and perioperative factors are associated with higher rates of complication in a low-resource setting, and are potentially modifiable to reduce complications following cleft surgery.